Why sub-Saharan African health workers migrate to European countries that do not actively recruit: a qualitative study post-migration - Annelien Poppe; Elena Jirovsky; Claire Blacklock; Pallavi Laxmikanth; Shabir Moosa; Jan De Maeseneer; Ruth Kutalek; Wim Peersman (2014)
BackgroundMany studies have investigated the migration intentions of sub-Saharan African medical students and health professionals within the context of a legacy of active international recruitment by receiving countries. However, many health workers migrate outside of this recruitment paradigm. This paper aims to explore the reasons for migration of health workers from sub-Saharan Africa to Belgium and Austria; European countries without a history of active recruitment in sub-Saharan Africa.MethodsData were collected using semistructured interviews. Twenty-seven health workers were interviewed about their migration experiences. Included participants were born in sub-Saharan Africa, had trained as health workers in sub-Saharan Africa, and were currently living in Belgium or Austria, though not necessarily currently working as a health professional.ResultsBoth Austria and Belgium were shown not to be target countries for the health workers, who instead moved there by circumstance, rather than choice. Three principal reasons for migration were reported: 1) educational purposes; 2) political instability or insecurity in their country of origin; and 3) family reunification. In addition, two respondents mentioned medical reasons and, although less explicit, economic factors were also involved in several of the respondents’ decision to migrate.ConclusionThese results highlight the importance of the broader economic, social, and political context within which migration decisions are made. Training opportunities proved to be an important factor for migration. A further development and upgrade of primary care might help to counter the common desire to specialize and improve domestic training opportunities.